مستوى البرولاكتين المصلي عند مرضى الصداف الشائع (Latakia University Journal -Medical Sciences Series, 2019)
Background: Prolactin may play a role in pathophysiology of psoriasis. Aim. To evaluate the correlation between serum PRL levels and Psoriasis Area and Severity Index (PASI) and duration of psoriasis . Material and methods: Serum PRL levels were measured in 61 patients ( 29 men,32 women age range 18,78 years) with psoriasis vulgaris. Most selected patients presented with chronic plaque psoriasis. Results were compared with a group of 61 controls. Results: Serum PRL levels were significantly increased in the psoriatic group compared with the control group (P-value=0,001). There was a positive correlation between serum PRL levels and the severity of psoriasis ( PASI score) (P-value= 0,02). Study also revealed a positive correlation between the duration of psoriasis and the serum levels of PRL (P-value=0,01). Conclusion:  Serum prolactin can be considered as marker for disease activity and duration in psoriatic patients. In addition, prolactin seems to have a role in pathogenesis of psoriasis.   مقدمة :قد يلعب البرولاكتين دوراً في الآلية الفيزيولوجية المرضية للصداف. هدف البحث: تقييم العلاقة بين مستوى البرولاكتين المصلي و مساحة الصداف ومشعر شدة الصداف و مدة الإصابة بالصداف. أدوات و طرائق البحث: تم قياس مستويات البرولاكتين لدى 61 مريضاً (29 ذكراً ,32 أنثى ,تراوحت أعمارهم بين 18, 78 سنة) مصابين بالصداف الشائع. كان معظم المرضى لديهم صداف لويحي مزمن. و تم مقارنة النتائج مع مجموعة شملت 61 شاهداً. النتائج: إن مستويات البرولاكتين المصلي كانت مرتفعة لدى مجموعة مرضى الصداف بالمقارنة مع مجموعة الشواهد ((P-value=0,001. وجد علاقة ارتباط إيجابي بين مستويات البرولاكتين المصلي و مشعر شدة الصداف مقدرة بال PASI score (P-value= 0,02). أظهرت الدراسة أيضاً علاقة ارتباط إيجابية بين مدة الإصابة بالصداف و مستوى البرولاكتين المصلي (P-value=0,01). الخلاصة: من الممكن اعتبار البرولاكتين المصلي مشعراً لشدة و مدة الإصابة بالصداف. و يبدو أن للبرولاكتين دوراً في إمراضية الصداف.